Etika Dakwah di Media Digital : Tantangan dan Solusi - Firman Maulidna; Khairatul Ulfi; Annisa Mulia; Ahmad Zuhri Ramadhan; Muhammad Saleh (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This paper discusses the challenges and ethical solutions in the practice of da'wah through digital media. In the rapidly developing digital era, platforms such as social media, blogs, and video sites provide unprecedented opportunities for Islamic da'wah to reach a global audience. However, the ease of dissemination of information also poses significant challenges, such as the spread of inaccurate information, negative or provocative content, and violations of regulations. This paper discusses these challenges and suggests solutions, including education and training for da'wah (preachers), the use of trusted platforms, collaboration with communication experts, and the development of digital da'wah ethics guidelines. This study uses a qualitative descriptive approach that aims to understand and describe the phenomenon of da'wah ethics in digital media in depth. Literature study is used as a data collection technique to explore the principles of da'wah ethics, the challenges faced by da'is in digital media, and the solutions proposed by communication and religious experts. This methodology allows researchers to gain a rich and holistic understanding of the challenges of digital da'wah ethics and their relevance in the context of modern communication. This study analyzes the impact of digital media on da'wah practices, with an emphasis on ethical considerations in content creation and interaction. It is concluded that da'wah in the digital era requires a careful and ethical approach to maintain the integrity and credibility of Islamic teachings while understanding the complexity of digital communication.